Exponential Increase in Size of Pineal Region Teratoma in Short Duration following Ventriculoperitoneal Shunt - Niraj Ghimire; Wajid Nazir Wani; Anita Jagetia; Daljit Singh (Indian Journal of Neurosurgery)
A 4-year-old male child presented with complaints of generalized tonic–clonic seizures for one and half years. Magnetic resonance imaging brain was suggestive of pineal region germ cell tumor with obstructive hydrocephalus. Patient had exponential increase in size of lesion following ventriculoperitoneal shunt for which patient underwent emergency craniotomy and tumor excision. Postoperative biopsy showed immature teratoma. Early diagnosis and complete resection of intracranial immature teratoma are must to have a favorable outcome, as delay in surgery may cause resection of tumor incomplete due to rapid increase in size of tumor following cerebrospinal fluid diversion.